Implementation of Accounting Standards for Non-Public Entities in Cooperative Financial Reporting - Syabani, Alfian Mirza; Kustinah, Siti (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
The application of Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) in the financial statements of the Civil Servants Cooperative of West Java Province (KPPP West Java) is essential to reflect accountability in managing the cooperative so that stakeholders can understand its financial condition. The primary objective of this research is to evaluate the suitability of adopting the SAK ETAP standards for the preparation of financial statements by KPPP West Java. The approach employed for this study is descriptive qualitative, involving the collection of data through interviews, observations, document analysis, and literature review. The information gathered from interviews and observations was systematically analyzed and compared to determine the compliance of the 2024 and 2023 financial statements of KPPP West Java with the SAK ETAP guidelines. The results found that the application of SAK ETAP was substantial deviation, accompanied by explanations of the deficiencies and suggestions for improvements in the financial statement presentation. The conclusion drawn is that the implementation of SAK ETAP in the financial statements of KPPP West Java is not yet appropriate, as it does not meet the minimum information requirements needed to fulfill the principles of transparency and accountability. Therefore, the recommended improvements are expected to assist KPPP West Java in preparing future financial statements in strict adherence to SAK ETAP, thereby enhancing transparency and stakeholder confidence.